2014
DOI: 10.1177/0899764014558933
|View full text |Cite
|
Sign up to set email alerts
|

The Local Embedding of Community-Based Organizations

Abstract: Although social organizations are considered a vital aspect of life in neighborhoods, research seldom examines how neighborhood context influences organizational vitality. This article considers how organizational and neighborhood characteristics influence organizational survival over time via a case study of immigrant organizations in Amsterdam. Using multilevel analysis, we investigate which features give organizations an advantage in uncertain environments and which neighborhood characteristics influence or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
55
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(57 citation statements)
references
References 42 publications
2
55
0
Order By: Relevance
“…For instance, being a political insideri.e. enjoying regular accessimproves the legitimacy an organization enjoys (Halpin & Thomas 2012;Vermeulen et al 2016;Baum & Oliver 1991). Additionally, the signal that political elites consider particular civil society organizations as relevant participants in the policy process might positively affect their ability to attract members and additional financial resources (Hager et al 2004;Baum & Oliver 1991;Fraussen 2014;Walker & McCarthy 2010;Mosley 2012).…”
Section: H1 Groups Who Are Engaged In Policy Domains Characterized Bmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, being a political insideri.e. enjoying regular accessimproves the legitimacy an organization enjoys (Halpin & Thomas 2012;Vermeulen et al 2016;Baum & Oliver 1991). Additionally, the signal that political elites consider particular civil society organizations as relevant participants in the policy process might positively affect their ability to attract members and additional financial resources (Hager et al 2004;Baum & Oliver 1991;Fraussen 2014;Walker & McCarthy 2010;Mosley 2012).…”
Section: H1 Groups Who Are Engaged In Policy Domains Characterized Bmentioning
confidence: 99%
“…The results are similar to what we report here. Yet, we decided not the included this control variable in the final model as resources and staff size are strongly correlated (r=.57; p<0.001) which caused problems of collinearity.6 A model with age as a quadratic term did not generate a significant impact(Hung & Ong 2012;Vermeulen et al 2016). 7 Comparing with a more parsimonious model, namely the full model without specific competition, we observe a much lower statistical fit, which confirms that this variable makes a substantial contribution to a better model fit (∆AIC=46.5).…”
mentioning
confidence: 99%
“…Unger and Wandersman ( 1985 ) particularly argued that the development of neighborhood organizations reflects the effects of neighboring (that is, social interaction, affective bonds, and neighborhood cognition). Two recent studies in the Netherlands (Vermeulen, Laméris, and Minkoff 2015 ;Vermeulen, Minkoff, and van der Meer 2016 ) examined this relationship using the concept of legitimacy, which implies that the needs and desires of organizations are accepted and supported by society.…”
Section: Consideration Of Location and Neighborhood Environmentmentioning
confidence: 99%
“…Some scholars have suggested that the analysis of organisational linkages is useful for studying legitimacy, as it places a single organisation within the wider field in which it is embedded (Baum and Oliver 1991;Vermeulen, Minkoff, and van der Meer 2016). Others have stressed that networks are crucial for understanding why organisations adopt specific organisational logics (Clemens and Cook 1999), or why certain groups are more powerful than others in public discursive struggles (Wimmer 2008).…”
Section: Literature Reviewmentioning
confidence: 99%
“…At the same time, organisational entrepreneurs may also discursively employ different types of linkages to gain legitimacy among third-party actors. Advertising those connections may suggest reliability and adherence to certain organisational values and principles (Baum and Oliver 1991), or rather convey support from the community it wishes to represent (Walker and McCarthy 2010;Vermeulen, Minkoff, and van der Meer 2016).…”
Section: Literature Reviewmentioning
confidence: 99%